Edukasi Kebiasaan Cuci Tangan 6 Langkah dengan Media Edukatif Permainan Ular Tangga - Wina Widianti; Nurshofi Intansari; Desty Yuliawati; Haryani; Rita Ayu Andira; Andre Maulana Putra; Ade Aji Fauzan (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction: Hands are one of the most common parts of the body where germs and bacteria are transmitted into the body, not maintaining hand hygiene can cause health problems such as diarrhea, especially in school-age children. Hand washing 6 steps is one of the efforts to prevent contracting a disease. Objective: The purpose of this health education is as an effort to increase knowledge and familiarize PHBS in washing hands from an early age in school-age children. Method: The research method uses observational methods, questions and answers and educational games. Result: The implementation of 6-step handwashing health education for 30 grade 4 students of SDN 1 Linggasari to prevent the spread of disease and create healthy living habits from an early age became the result of this outreach activity. Conclussion: This 6-step handwashing health education was attended by 30 4th grade students at SDN 1 Linggasari and was running optimally.